2011
DOI: 10.1177/1040638711404154
|View full text |Cite
|
Sign up to set email alerts
|

Minimum inhibitory concentrations of selected antimicrobial agents forMoraxella bovoculiassociated with infectious bovine keratoconjunctivitis

Abstract: Moraxella bovoculi is a recently identified species of Moraxella first characterized in 2007. 10 The original 18 characterized isolates were cultured from the ulcerated eyes of calves with infectious bovine keratoconjunctivitis (IBK; "pinkeye") in northern California during summer of 2002. 10 At the present time, it is not known if M. bovoculi plays a primary or secondary role in the pathogenesis of IBK; to date, no published reports have demonstrated Koch's postulates for M. bovoculi and IBK. Nevertheless, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
1
16
2
Order By: Relevance
“…M. bovis strains presented a significant higher resistance against cloxacillin, cotrimoxazole and tetracycline compared to M. bovoculi. Although Angelos et al [21] found a 3.5% of resistant M. bovoculi to oxytetracycline, in our study all the isolates were sensitive against this antibiotic. The difference observed in resistant pattern against antibiotics between M. bovis and M. bovoculi may have implications in the pathogenicity and the treatment of IBK.…”
Section: Discussionmentioning
confidence: 45%
“…M. bovis strains presented a significant higher resistance against cloxacillin, cotrimoxazole and tetracycline compared to M. bovoculi. Although Angelos et al [21] found a 3.5% of resistant M. bovoculi to oxytetracycline, in our study all the isolates were sensitive against this antibiotic. The difference observed in resistant pattern against antibiotics between M. bovis and M. bovoculi may have implications in the pathogenicity and the treatment of IBK.…”
Section: Discussionmentioning
confidence: 45%
“…The antimicrobial resistance patterns appear similar between geographically distinct M. bovis and M. bovoculi isolates, indicating that infections with either or both organisms show similar susceptibility patterns as previously noted. 5 However, it should be noted that there are some small differences, as the MIC 90 of M. bovoculi for oxytetracycline was higher than for M. bovis (4 µg/ml compared with 1 µg/ml).…”
Section: Discussionmentioning
confidence: 96%
“…Susceptibility testing was carried out as previously described 9. Streptococci and Pasteurella species were inoculated into cation-adjusted Mueller-Hinton broth containing laked horse blood before inoculation of Sensititre plates, sealed with perforated seals and incubated with 5 per cent CO 2 .…”
Section: Methodsmentioning
confidence: 99%